Association of free-prostate specific antigen subfractions and human glandular kallikrein 2 with volume of benign and malignant prostatic tissue. - Steuber, T; Niemela, P; Haese, A; Pettersson, K; Erbersdobler, A; Felix Chun, K; Graefen, M; Kattan, M; Huland, H; Lilja, H (2005)
BACKGROUND: We investigated the association of different subfractions of prostate specific antigen (PSA) and human glandular kallikrein 2 (hK2), such as total PSA (tPSA), complexed PSA (cPSA), free PSA (fPSA), "single-chain Intact fPSA" (fPSA-I), "multi-chain nicked fPSA" (fPSA-N), and total hK2 with volumes of total prostate gland, transition zone (tz), and prostate cancer (PCa) tissue in patients with benign and malignant prostatic disease. METHODS: Serum samples were collected from men with negative biopsy (n=164) and PCa (n=252). Total and fPSA were measured using a commercially immunoassay. We measured hK2 and fPSA-I by previously reported in-house research assays specific for hK2 and single-chain, non-cleaved fPSA, respectively. Levels of fPSA-N (=fPSA-fPSA-I) and cPSA (=tPSA-fPSA) were calculated. Total prostate and tz volume were measured using transrectal ultrasound (TRUS); PCa volume was calculated using a computer assisted volumetric program. Association with tz and cancer volumes (CaVols) was performed by linear regression analysis. RESULTS: All PSA subfractions and hK2 were associated with tz volume in multivariable linear regression analysis. Only hK2, fPSA, and fPSA-N were significantly associated with CaVol in multivariable analysis, fPSA-I seemed to be cancer related. CONCLUSIONS: The multi-chain fPSA-N subfractions of fPSA may be a valuable predictor of both benign prostate hyperplasia (BPH) and CaVol that is likely to be more useful in predicting tz volumes than CaVols. fPSA-I may provide information on cancer without being influenced by the presence of BPH.